OP0098 SUICIDAL BEHAVIOUR IN FIBROMYALGIA PATIENTS: META-ANALYSIS AND SYSTEMATIC REVIEW OF THE LITERATURE. (June 2019) - Adawi, Mohammad; Bragazzi, Nicola Luigi; Mcgonagle, Dennis; Watad, Abdulla; Amital, Howard
Abstract : Background: Suicide is a leading cause of death worldwide, with approximately 800, 000 people dying every year. Fibromyalgia is the second most common rheumatic disease, affecting 0.2-6.6% of the population worldwide and fibromyalgia patients suffer from anxiety and depression, which are known to be risk factors for suicidal behaviour. Suicidality related to chronic pain conditions has been studied, but there is a dearth of information specifically concerning suicidality among patients with fibromyalgia. Objectives: To investigate the risk of suicidal ideation and attempts in patients with fibromyalgia. Methods: A systematic review and meta-analysis was conducted and reported according to the "Preferred Reporting Items for Systematic reviews and Meta-analyses" (PRISMA) standards. Also, the gray literature was extensively searched. Results: Thirteen studies were included in the present systematic review and meta-analysis, of 394, 087 fibromyalgia patients. Sample size ranged from 44 to 199, 739 subjects: mean age ranged from 45.8 to 54.5 years while female percentage went from 17.1% to 100.0%. Fibromyalgia diagnosis was based on the 1999 ACR criteria and 2010 ACR criteria in one study. The overall suicide ideation prevalence was 29.57% (95%CI 1.84-72.07), with an OR 9.12 of (95%CI 1.42-58.77), ranging from 2.34 (95%CI 1.49-3.66) to 26.89 (95%CI 5.72-126.42). Pooled suicide attempt prevalence was 5.69% [95%CI 1.26-31.34], with an OR of 3.12 [95%CI 1.37-7.12]. Suicide risk was higher with respect to the general population with an OR of 36.77 (95%CI 15.55-96.94), as well as suicide events with an HR of 1.38 (95%CI 1.17–1.71). Determinants of suicidality were found to be: employment status, disease severity, obesity and drug dependence, chronic pain and co-morbidities, in particular depression, anxiety, poor sleep, and global mental health. Conclusion: Fibromyalgia patients are particularly prone to suicide, in terms of ideation, attempt, risk and events, warranting a pre-emptive screening of their mental health status. However, in some cases, after adjusting for psychiatric conditions, the threshold of statistical significance was not achieved. Given the few studies available, the high amount of heterogeneity and the evidence of publications bias, further high-quality studies should be conducted. Disclosure of Interests: Mohammad Adawi: None declared, Nicola Luigi Bragazzi: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB, Abdulla Watad: None declared, Howard Amital Grant/research support from: Pfizer, AbbVie, Janssen, Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Merck Sharp & Dohme, Consultant for: Pfizer, Merck Sharp & Dohme, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm